Survival Factors and Metabolic Pathogenesis in Elderly Patients (≥65) With COVID-19: A Multi-Center Study - Mei, Qi; Wang, Amanda Y.; Bryant, Amy; Yang, Yang; Li, Ming; Wang, Fei; Du, Shangming; Kurts, Christian; Wu, Patrick; Ma, Ke; Wu, Liang; Chen, Huawen; et al. (Frontiers in Medicine, 2021)
Background Elderly patients infected with COVID-19 are reported to have a substantially increased risk of mortality. Clinical characteristics, treatment options, and potential survival factors remain under investigation. This study aimed to fill this gap and provide clinically relevant factors associated with survival of elderly patients with COVID-19. Methods In this multi-center study, elderly patients (age ≥65 years old) with laboratory-confirmed COVID-19 from 4 Wuhan hospitals were included. The clinical end point was hospital discharge or deceased with last date of follow-up on Jul. 08, 2020. Clinical, demographic, and laboratory data were collected. Univariate and multivariate analysis were performed to analyze survival and risk factors. A metabolic flux analysis using a large-scale molecular model was applied to investigate the pathogenesis of SARS-CoV-2 regarding metabolism pathways. Results A total of 223 elderly patients infected with COVID-19 were included, 91 (40.8%) were discharged and 132 (59.2%) deceased. Acute respiratory distress syndrome (ARDS) developed in 140 (62.8%) patients, 23 (25.3%) of these patients survived. Multivariate analysis showed that potential risk factors for mortality were elevated D-Dimer (odds ratio: 1.13 [95% CI 1.04 - 1.22], p=.005), high immune-related metabolic index (6.42 [95% CI 2.66 - 15.48], p<.001), and increased neutrophil-to-lymphocyte ratio (1.08 [95% 1.03 - 1.13], p<.001). Elderly patients receiving interferon atmotherapy showed an increased probability of survival (0.29 [95% CI 0.17 - 0.51], p<.001). Based on these factors, an algorithm (AlgSurv) was developed to predict survival for elderly patients. The metabolic flux analysis showed that 12 metabolic pathways including phenylalanine (odds ratio: 28.27 [95% CI 10.56 - 75.72], p<0.001), fatty acid (15.61 [95% CI 6.66 - 36.6], p<0.001), and pyruvate (12.86 [95% CI 5.85 - 28.28], p<0.001) showed a consistently lower flux in the survivors versus deceased. This may reflect a key pathogenic mechanism of COVID-19 infection. Conclusion Several factors such as interferon atmotherapy and recreased activity of specific metabolic pathways were found to be associated with survival of elderly patients. Based on these findings, a survival algorithm (AlgSurv) was developed for clinical stratification of elderly patients. Dysregulation of the metabolic pathways revealed here may aid in the drug and vaccine development against COVID-19.